TIPOLOGI KEPEMIMPINAN DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM DI MADRASAH - Fauzi Fahmi; Wahyu Iskandar (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2020)
Stakeholder ideas and ideas in their reactualization never stop contributing discourse to change in the field of education. The leaders of educational institutions have full responsibility in carrying out improving the quality of education. This study aims to introduce leadership typologies in improving the quality of Islamic education in madrasas, ranging from the type of leadership, the leadership process of madrasa heads to the implementation of leadership in madrassas in improving quality. This research uses a literature study method. As for the results of this study indicate the role of leadership in carrying out its duties to members include: (a) Making decisions. (b) Developing the imagination; (c) Developing the loyalty of followers; (d) Control of the plan; (e) Utilizing human resources and other resources. (f) Carry out controls and corrections for errors; (g) Give a token of appreciation; (h) Delegating authority to subordinates; (i) Implement decisions by giving encouragement to followers.